(untitled) (Journal of the College of Basic Education, 2022)
The development in the field of design research has made important leaps that have moved it to new fields that did not exist previously. As a result of the interaction of this science in the various aspects of life, the achievement of design effectiveness has become not limited to meeting the functional and aesthetic requirements only, but rather the transition to design to address the motives of human behavior and its interests as a result of data. The modern era, whose developments (production, marketing, competition, etc.) constituted pressure forces on the design act, necessitated its thinkers to devise new methods by which they reduce time and shorten distances in order to make their design policies succeed according to the growing expectations and needs of consumers on the one hand, and the growing competition market on the other hand. .